The Other Woman: A Feminist-Existentialist Analysis of Anora (2024) - Azis, Kamal Abdul; Nurhayati, Sulasih; Nirmalawati, Widya; Ernawati, Asih (Universitas Muhammadiyah Barru, 2026)
This study analyzes the representation of female subjectivity, freedom, and agency in Anora (2024) through the lens of Sartre’s existentialism and Beauvoir’s existential feminism. It examines how Ani negotiates her existential autonomy by resisting patriarchal constructions that position her as “the Other.” Employing a qualitative descriptive approach based on dialogue transcripts, repeated viewing, and close analysis of key interactions, the data were selected according to thematic relevance to radical freedom, authenticity, and objectification. The findings show that Ani affirms herself as a responsible and choosing subject while resisting gendered labels and social objectification through her speech and actions. Her refusal to accept a subordinate identity and her insistence on the legitimacy of her marriage illustrate an existential struggle against imposed roles within patriarchal kinship structures. Rather than depicting liberation as triumphant, the film portrays women’s freedom as situated, relational, and constrained by class and institutional power. This study demonstrates that philosophical frameworks are essential for understanding how contemporary cinema visualizes feminine identity, agency, and the limits of existential freedom within oppressive social systems.